Effect of Dolomite Lime on pH and H2S of Mangrove Acid Soil - Nugraha, Bagas Aditya; Purnomo, Pujiono Wahyu; Rahman, Arif (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2023)
Generally, the soil where mangroves grow is soil that has a low level of maturity. The soil around the mangrove forest is a source of pyrite (iron sulfide), so it has a low pH. Using lime will help increase the soil pH so that it is not too acidic. One of the materials used for liming is dolomite lime. The research objective was to determine changes in the concentration of pH, H2S, and nitrate on dolomite lime and to determine the effect of differences in concentrations between those with added dolomite and those not added. This research is experimental with dolomite treatment respectively 6 g, 12 g and 12 g. The variables measured were pH, H2S, and nitrate. The measurement time is for 9 days with an interval of every 3 days. The data analysis used was variance (ANOVA).The results of the ANOVA test showed that dolomite lime had an effect on pH and H2S (α <0.05) and had no effect on the nitrate variable (α> 0.05).